2001
DOI: 10.1165/ajrcmb.25.1.4481
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Growth Factor- β1Overexpression in Tumor Necrosis Factor- α Receptor Knockout Mice Induces Fibroproliferative Lung Disease

Abstract: Tumor necrosis factor-alpha receptor knockout (TNF-alphaRKO) mice have homozygous deletions of the genes that code for both the 55- and 75-kD receptors. The mice are protected from the fibrogenic effects of bleomycin, silica, and inhaled asbestos. The asbestos-exposed animals exhibit reduced expression of other peptide growth factors such as transforming growth factor (TGF)-alpha, platelet-derived growth factors, and TGF-beta. In normal animals, these and other cytokines are elaborated at high levels during th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
46
0
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(50 citation statements)
references
References 12 publications
2
46
0
2
Order By: Relevance
“…TNFα is a multifunctional cytokine implicated in the pathogenesis of a number of pulmonary disorders including acute respiratory distress syndrome and idiopathic pneumonia, as well as tissue injury induced by endotoxin, bleomycin, silica and asbestos (Liu et al, 2001;Pryhuber et al, 2003;Shimabukuro et al, 2003;Bhatia and Moochhala, 2004;Zhao et al, 2004;Shukla et al, 2005;Ke et al, 2006;Mukhopadhyay et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…TNFα is a multifunctional cytokine implicated in the pathogenesis of a number of pulmonary disorders including acute respiratory distress syndrome and idiopathic pneumonia, as well as tissue injury induced by endotoxin, bleomycin, silica and asbestos (Liu et al, 2001;Pryhuber et al, 2003;Shimabukuro et al, 2003;Bhatia and Moochhala, 2004;Zhao et al, 2004;Shukla et al, 2005;Ke et al, 2006;Mukhopadhyay et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…10,11 Our laboratory and others have demonstrated that expression of a constitutively active form of TGF-b 1 through an adenovirus vector in the lungs of rats and mice induces fibrogenesis. 15,16,31 This treatment causes scarring even in fibrogenicresistant TNF-a double receptor KO mice. 16 Similar expression of the full latent TGF-b 1 complex fails to initiate this fibrogenic response.…”
Section: Discussionmentioning
confidence: 99%
“…15,16,31 This treatment causes scarring even in fibrogenicresistant TNF-a double receptor KO mice. 16 Similar expression of the full latent TGF-b 1 complex fails to initiate this fibrogenic response. 15 Because latent TGF-b 1 is constitutively produced in the lung by a number of cell types, including type II epithelial cells 32 and macrophages, 10 it is essential that the mechanisms which free the active TGF-b 1 peptide from its LAP be elucidated to understand the precise biological roles of TGF-b 1 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations